Frizzled-2 small interfering RNA protects hepatic BRL-3A cells against Hypoxia / Reoxygenation via modulation of autophagy - Xiang Hu,; Xiang Hu,; Chenjie Zhou,; Guolin He,; Yuan Cheng,; MingXin Pan,; Yi Gao, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Autophagy plays a positive role in the prevention of liver damage after hepatic ischemia-reperfusion injury (HIRI); however, the molecular mechanism is still a mystery. Understanding the molecular events behind this injury may have important implications for devising proper strategies for managing liver injury. This study investigated the effects of Frizzled-2 expression on autophagy as well as Ca2+ concentration and apoptosis in BRL-3A cells.Materials and Methods: BRL-3A cells exposed to the hypoxia/reoxygenation (H/R) condition were used as an in vitro HIRI hepatic cell model. The transfection of Frizzled-2 small interfering RNA (siRNA) or expression vector was performed to silence or overexpress Frizzled-2 in BRL-3A cells. The intracellular Ca2+ concentration was monitored by the fluorescence of Ca+. Western blot was used to detect autophagy-related proteins and apoptotic marker Caspase-3. The cellular autophagosome was observed by a transmission electron microscope.Results: Beclin-1 and Atg7 expressions were considerably induced by H/R treatment, and this induction was attenuated by Frizzled-2 siRNA in BRL-3A cells. The LC3B-II/I ratio was inhibited by H/R treatment, although it was considerably induced by Frizzled-2 siRNA. The overexpression of Frizzled-2 induced intracellular Ca2+ concentration and expressed autophagy-related proteins and Caspase-3 except for the suppression of LC3B-II/I ratio in BRL-3A cells in the normoxia condition.Conclusion: The overexpression of Frizzled-2 mimicked H/R treatment and suppressed autophagy activity, whereas Frizzled-2 siRNA induced cellular autophagy and attenuated the H/R-induced hepatic injury in BRL-3A cells. These developments suggest that Frizzled-2 siRNA protects hepatic BRL-3A cells from the injury of H/R via autophagy modulation.Cite this article as: Hu X, Zhou C, He G, Cheng Y, Pan M, Gao Y. Frizzled-2 small interfering RNA protects hepatic BRL-3A cells against Hypoxia / Reoxygenation via modulation of autophagy. Turk J Gastroenterol 2020; 31(2): 167-79.